Smart Contract Blockchain for Supporting Therapy of Neurological Patients - U. А. Vishniakou; Yu Chuyue (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2025)
The scientific novelty of the article is the technology of using a medical blockchain based on a smart contract to support patient therapy after IT diagnosis of Alzheimer’s disease. In combination with the subsystem of IT diagnostics of a patient, the exchange of recognition data for the degree of Alzheimer’s disease is implemented. The smart contract performs automated management of therapy support for patients with diagnosed Alzheimer’s disease . The functional structure of the therapy support subsystem (smart contract in the Etherium blockchain) has been developed, including initialization of patient data, treatment plans, registration of medical staff, record management, dynamic switching of therapy plans based on diagnostic data, monitoring of medical staff warnings, as well as management of payments and their distribution. The proposed smart contract enables a new approach to interaction and collaboration in the field of therapy management and can be used for neurological patients with other diseases.